Resilient City : The Economic Impact of 9/11 - Chernick, Howard (Book collections on Project MUSE., 2005)
"Assessing multiple facets of the New York City economy in the years after 9/11, Resilient City discerns many hopeful signs among persistent troubles. Analysis by economist Sanders Korenman indicates that the value of New York-based companies did not fall relative to other firms, indicating that investors still believe that there are business advantages to operating in New York despite higher rates of terrorism insurance and concerns about future attacks. Cordelia W. Reimers separates the economic effects of 9/11 from the effects of the 2001 recession by comparing employment and wage trends for disadvantaged workers in New York with those in five major U.S. cities. She finds that New Yorkers fared at least as well as people in other cities, suggesting that the decline in earnings and employment for low-income New York workers in 2002 was due more to the recession than to the effects of 9/11. Still, troubles remain for New York City. Howard Chernick considers the substantial fiscal implications of the terrorist attacks on New York City, estimating that the attack cost the city about three billion dollars in the first two years alone; a sum that the city now must make up through large tax increases, spending cuts, and substantial additional borrowing, which will inevitably be a burden on future budgets." "The terrorist attacks of 9/11 dealt a severe blow to the economy of New York City, but it was far from a knock-out punch. Resilient City shows that New York's dynamic, flexible economy has absorbed the pain and hardships of the attacks, and provides a thorough, authoritative assessment of what, so far, has been a strong recovery for New York."--Jacket